2015
DOI: 10.1119/1.4902185
|View full text |Cite
|
Sign up to set email alerts
|

Particle dynamics in damped nonlinear quadrupole ion traps

Abstract: Articles you may be interested in Erratum: "Averaging peak-to-peak voltage detector for absolute mass determination of single particles with quadrupole ion traps" [Rev. Sci. Instrum.76, 023108 (2005) We examine the motions of particles in quadrupole ion traps as a function of damping and trapping forces, including cases where nonlinear damping or nonlinearities in the electric field geometry play significant roles. In the absence of nonlinearities, particles are either damped to the trap center or ejected, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
0
26
0
6
Order By: Relevance
“…Since the depth of the effective potential is inversely proportional to the frequency, Φ n[1] ∝1/Ω 2 from (16), this configuration is suitable to localize even particles of more than 10 −5 m size [20,33,34]. Localization dynamics of such particles is in agreement with the model of nonlinear damping [20], which allows to estimate the quasi-equilibrium points taking into account cubic nonlinearities (discussed in section 2.2). Figure 4(a) illustrates the experimental realization of a particle localization inside and outside of the Paul trap, which is indicated by areas A and B, correspondingly.…”
Section: Experimental Confirmation Of Outside Localizationmentioning
confidence: 63%
See 3 more Smart Citations
“…Since the depth of the effective potential is inversely proportional to the frequency, Φ n[1] ∝1/Ω 2 from (16), this configuration is suitable to localize even particles of more than 10 −5 m size [20,33,34]. Localization dynamics of such particles is in agreement with the model of nonlinear damping [20], which allows to estimate the quasi-equilibrium points taking into account cubic nonlinearities (discussed in section 2.2). Figure 4(a) illustrates the experimental realization of a particle localization inside and outside of the Paul trap, which is indicated by areas A and B, correspondingly.…”
Section: Experimental Confirmation Of Outside Localizationmentioning
confidence: 63%
“…In sufficiently dense medium, the motion of a charged particle is damped. For instance, it was reported that particles of the size bigger than 10 μm undergo a strong nonlinear friction upon the localization in air, which results in unusual expanded orbits [20].…”
Section: Calculation Of Effective Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…Other relevant quantities are the gas viscosity coefficient µ, the particle diameter d p , the particle mass m, while b represents the geometrical constant of the electrodynamic balance. harmonically confines ions in a region where the field exhibits a minimum, under conditions of dynamic stability 6, 16,22,28,59,75 . As it is almost impossible to achieve quadratic a.c. and d.c. endcap potentials for the whole trap volume, it can be assumed that the potential in the vicinity of the trap axis region can be regarded as harmonic, which is a sufficiently accurate approximation.…”
Section: Microparticle Dynamics Strongly Coupled Coulomb Systemsmentioning
confidence: 99%